Aerospace Meteorology: An Overview of Some Key Environmental Elements - Vaughan,William W. (2013)
ABSTRACT: The natural terrestrial environment plays a significant role in the design and operation of aerospace vehicles (space vehicles and rockets) and in the associated integrity of aerospace systems and elements. Addressed herein are some of the key vehicle and environment areas of concern plus "lessons learned" that have been identified over a number of years. Many of these aerospace meteorology related events occurred during the development and interpretation of natural environment inputs, especially those of terrestrial environment, used in the design and development of the Saturn Apollo and Space Shuttle vehicles plus associated mission operations. Background is given regarding the actions needed to avoid having to re-learn these lessons.